Novel Lossless Positive-/Negative-Grounded Capacitance Multipliers Using VCII - Mohammad Faseehuddin; Sadia Shireen; Sawal Hamid Md Ali; Worapong Tangsrirat (My University, 2023)
In the presented research, the second-generation voltage conveyor (VCII) is used in the design of active capacitance multipliers. In this paper, three positive and one negative lossless grounded capacitance multipliers (GCMs) are designed. All of these GCMs are designed using two VCIIs, one capacitor, and two resistors. There is no need for any passive component matching to implement a GCM. The multiplication factor of GCMs can be set/varied by changing the values of two resistances as per requirement. Considering nonideal constraints, GCMs are analysed mathematically to evaluate the effect of nonideal current and voltage transfer gains on the performance of the proposed GCMs. Also, parasitic analysis is conducted to study the effect of VCII node impedance on the performance of the presented GCMs. The simulation analysis is performed using Cadence Virtuoso in 0.18 µm Silterra Malaysia process design kit (PDK). Additionally, the macro-model of commercially available integrated circuit, AD844, is used to design the proposed GCM-2 to further prove the theoretical findings.
Keywords: Advancements in Semiconductor Devices and Circuit Design